Influence of herbicides on yield, nodulation and physiological quality of soybean seeds - Rezende, Pedro Milanez de; Vieira, Maria das Graças Guimarães Carvalho; Vieira Neto, José Caetano; Alcântara, Elifas Nunes de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at the Escola Superior de Agricultura de Lavras, Lavras, MG, Brazil, during the growing season of 1978-1979, to study the influence of herbicides on grain yield, nodulation and physiological quality of soybean (Glycine max (L.) Merrill) seeds, using the cultivar UFV-1, in Dystrophic Dusky Read Latosol. The treatments were: handweeded, unweeded, fluorodifen (0.90 kg/ha), pendimethalin (0.75 kg/ha), fluorodifen + pendimethalin (0.45 + 0.37 kg/ha) chloramben (1.91 kg/ha), trifluralin (0.47 kg/ha), and chloramben + alachlor (0.95 + 0.66 kg/ha). AlI the herbicides were applied as pre-emergence treatments except trifluralin as incorporated preplant. The herbicides showed similar behavior and provided grain yield from 99.94% to 82.68% compared with the handweed control. Nodulation, final stand, germination and seedling vigor were not affected by the treatments.